Enhancing tensile strength of Mg–Al–Ca wrought alloys by increasing Ca concentration. (July 2020) - Huang, Qiuyan; Liu, Yang; Tong, Min; Pan, Hucheng; Yang, Changlin; Luo, Tianjiao; Yang, Yuansheng
Abstract: The tensile strengths of the as-extruded Mg–Al–Ca ternary alloys at both ambient and elevated temperatures are enhanced via adding a high content of Ca element up to 6 wt%. High-temperature strength of the present rare-earth-free Mg alloys can be even compared with those of the reported Mg-RE alloys. The as-extruded Mg–6Al–6Ca (wt. %, AX66) alloy exhibits a tensile yield strength (YS) of ~404 MPa and an ultimate tensile strength (UTS) of ~415 MPa at room temperature, and YS of ~225 MPa and UTS of ~265 MPa at 200 °C, respectively. For the AX66 alloy, the nucleation rates of dynamic recrystallized (DRXed) grains are larger than those of the AX62 and AX64 alloys due to the typical particle stimulated nucleation effect. A number of long-rod Al2 Ca phase is dispersed at the grain boundaries of AX66 alloy, and a restricted degree of DRX is induced. Consequently, the majority ofα-Mg matrix exists in the as-deformed state involving a high density of subgrains. The combined effects of grain refinement hardening, texture hardening and precipitation hardening guarantee the high strength. Specially, numerous micron-scale bulk (Mg, Al)2 Ca phases are found to distribute among matrix, which play a critical role in maintaining the high thermal-resistance. Highlights: With the increasing the Ca content, strengths of Mg–Al–Ca alloys at both room temperature and 200 °C gradually increase. In the AX66 alloy with highest amount of Ca content, the nucleation rate of DRXed grains is large due to the typical PSN effect. A restricted degree of DRX would be induced in the AX66 alloy due to the formations of profuse nano-Al2 Ca phases. The high amounts of micron-scale bulk (Mg, Al)2 Ca phases should play the critical role in maintaining the high thermal resistance.